Scientometric Study of The World Academic Production in Reproductive Medicine And COVID-19 - Carlos Quispe-Vicuna; Miguel Cabanillas-Lazo; Carlomagno Villarreal-Inca; Maria Eugenia Guerrero; John Barja-Ore; Abigail Temoche; Mayta-Tovalino, Frank (National Journal of Community Medicine, 2023)
Background: COVID-19 has generated new gaps in knowledge, which in turn has had a significant impact on different areas of research, one of these being Reproductive Medicine. However, to date, no analysis of publications on this topic has been identified. Therefore, the aim of this study was to perform a bibliometric analysis of the worldwide scientific production of COVID-19 in Reproductive Medicine. Method: We conducted an advanced bibliographic search in the Scopus database to identify articles on COVID-19 and Reproductive Medicine from 2019 to May 2022. The collected data was analyzed with Scival software, and the results were presented through summary tables. Result: A total of 737 publications were collected and analyzed, of which 594 were original articles and 143 reviews. Leila V. Adamyan and Sechenov First Moscow State Medical University (Russia) were the most productive author and institution, respectively. The European Journal of Obstetrics, Gynecology and Reproductive Biology was the journal with the highest number of publications. In addition to that, we report a steady increase in the number of publications between 2020 and 2021, especially of articles published in first quartile (Q1) journals. Finally, although most of the publications had only national collaboration, the highest impact was found in those studies with international collaboration. Conclusion: The scientific production on Reproductive Medicine and COVID-19 has reported a steady increase in recent years, especially in Q1 journals, which evidences a special interest in the subject by the scientific community. However, since new articles on COVID-19 are constantly being published, we recommend future bibliometric analyses to better analyze the topic.